Metacognition in listening comprehension: Analyzing strategies and gender differences among Saudi EFL University students - Mohammad H. Al-Khresheh; Shatha F. Alruwaili (Cogent Social Sciences, 2024)
This quantitative study explores metacognitive listening comprehension strategies among Saudi EFL students, aiming to identify the most and least utilized strategies and examine potential gender differences. Employing a descriptive research design, data were collected randomly from 204 Saudi male and female university students across various academic levels using the “Metacognitive Awareness Listening Questionnaire”. Descriptive statistical analysis, conducted via SPSS, revealed that problem-solving and mental translation were the most frequently employed strategies, indicating proactive identification and resolution of listening challenges and significant reliance on language conversion for comprehension. Planning, evaluation, directed attention, and person knowledge were also utilized, albeit to a lesser extent. Gender analysis indicated no significant differences in strategy utilization, except for problem-solving, where females exhibited a higher propensity. These findings offer insights into the metacognitive strategies prevalent among Saudi EFL students and highlight the need for gender-sensitive pedagogical approaches in EFL instruction.